Profilin-1 deficiency leads to SMAD3 upregulation and impaired 3D outgrowth of breast cancer cells. Issue 9 (30th October 2018) - Chakraborty, Souvik; Jiang, Chang; Gau, David; Oddo, Michael; Ding, Zhijie; Vollmer, Laura; Joy, Marion; Schiemann, William; Stolz, Donna; Vogt, Andreas; Ghosh, Sujoy; Roy, Partha
Abstract Background Adhesion-mediated activation of FAK/ERK signalling pathway, enabled by the formation of filopodial protrusions (FLP), has been shown to be an important event for triggering of dormancy-to-proliferation switch and metastatic outgrowth of breast cancer cells (BCC). We studied the role of actin-binding protein profilin1 (Pfn1) in these processes. Methods Quantitative immunohistochemistry (IHC) of BC tissue microarray (TMA) and survival analyses of curated transcriptome datasets of BC patients were performed to examine Pfn1's association with certain clinicopathological features. FLP formation and single cell outgrowth of BCC were assessed using a 3D matrigel culture that accurately predicts dormant vs metastatic outgrowth phenotypes of BCC in certain microenvironment. Gene expression studies were performed to identify potential biological pathways that are perturbed under Pfn1-depleted condition. Results Lower Pfn1 expression is correlated with lower nuclear grade of breast tumours and longer relapse-free survival of BC patients. Pfn1 depletion leads to defects in FLP and outgrowth of BCC but without impairing either FAK or ERK activation. Guided by transcriptome analyses, we further showed that Pfn1 depletion is associated with prominent SMAD3 upregulation. Although knockdown and overexpression experiments revealed that SMAD3 has an inhibitory effect on the outgrowth of breast cancer cells, SMAD3 knockdown alone was not sufficient to enhance the outgrowth potential of Pfn1-depleted BCC suggesting that other proliferation-regulatory pathways in conjunction with SMAD3 upregulation may underlie the outgrowth-deficient phenotype of BCC cells upon depletion of Pfn1. Conclusion Overall, these data suggest that Pfn1 may be a novel biomarker for BC recurrence and a possible target to reduce metastatic outgrowth of BCC.